Behavior and Marketing Mix Factors Influencing on the Consumption of Street Food by Thai Tourists in the Municipal Area of Nakhon Phanom Province - Meauipa, Natthida; Saengtong, Jiraporn; Khakhanmanee, Buntham (RMUTK Journal of Liberal Arts, 2023)
This research aims to study the street food eating behavior of Thai tourists. In the municipal area of Nakhon Phanom province, and to study Marketing Miz factors that influence the consumption of street food by Thai tourists in the municipal are of Nakhon Phanom Province. The study is quantitative research, collecting data from a sample group of Thai tourists traveling within the municipal area of Nakhon Phanom. The sample size is 400 individuals, selected through random sampling. The Index of Item Objective Congruence (IOC) was employed to ensure questionnaire validity, with each item having a congruence index exceeding 0.50. The questionnaire's reliability, with a value of 0.70, is considered acceptable for survey research (Hair and colleagues: 2006). The results of the research reveal that there are significant relationships between tourists' gender, occupation, and average monthly income, leading to different street food consumption behaviors. The statistical significance level is found to be less than 0.05. Additionally, the relationship between tourists of different genders, statuses, and ages differs in factors influencing their decision-making in consuming street food with statistically significant differences in the levels of significance below 0.05.